2018
DOI: 10.1093/jnen/nly075
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Intra-Axial Malignant SMARCB1-Deficient Desmoplastic Tumor Arising in Meningioangiomatosis

Abstract: SMARCB1 inactivation is a well-established trigger event in atypical teratoid/rhabdoid tumor. Recently, a role for SMARCB1 inactivation has emerged as a mechanism of clonal evolution in other tumor types, including rare brain tumors. We describe an unusual malignant intra-axial SMARCB1-deficient spindle cell desmoplastic neoplasm, occurring in a 6-year-old child with meningioangiomatosis and a long history of seizures. Striking features of the tumor were a storiform pattern and strong CD34 expression. Undiffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Molecular analyses of the meningioangiomatosis and sarcoma in this case showed that the meningioangiomatosis exhibited multiple recurrent chromosomal alterations including monosomy 22, 6q gain, and 5q loss. Interestingly, monosomy 22 and 6q gain were also observed in the sarcomatous lesion, in addition to numerous other chromosomal alterations, suggesting that the tumor may have arisen from the underlying meningioangiomatosis through acquisition of additional chromosomal alterations and silencing of SMARCB1 expression [113].…”
Section: Meningioangiomatosismentioning
confidence: 99%
“…Molecular analyses of the meningioangiomatosis and sarcoma in this case showed that the meningioangiomatosis exhibited multiple recurrent chromosomal alterations including monosomy 22, 6q gain, and 5q loss. Interestingly, monosomy 22 and 6q gain were also observed in the sarcomatous lesion, in addition to numerous other chromosomal alterations, suggesting that the tumor may have arisen from the underlying meningioangiomatosis through acquisition of additional chromosomal alterations and silencing of SMARCB1 expression [113].…”
Section: Meningioangiomatosismentioning
confidence: 99%
“…Only six cases occurred in the occipital lobe (9.68%). Intracranial lesions coexisting with MA have been reported in 17 patients [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], and meningioma was the most common combined tumor (11/17, 64.71%) [ 9 , 10 , 13 , 14 , 15 ]. Notably, the perivascular spread of meningioma-associated-type MA should not be interpreted as evidence of a grade II meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lucila Domecq Laplace et al [ 27 ] reported three cases of CAPNON located in the posterior fossa with perilesional edema, and the vast majority were cured after total resection. However patients may experience recurrence because of incomplete evacuation [ 28 ], neoplastic malignancy [ 12 ], or coexisting with other malignant tumors [ 20 , 21 ]. In addition to surgery, medical treatment and follow-up observations have been reported [ 1 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…SMARCB1/INI1 is a component of the SWI/SNF complex that is involved in chromatin remodeling and transcriptional regulation 4 . Inactivation of SMARCB1/INI1 has been detected in many CNS tumors, including AT/RT, extraskeletal myxoid chondrosarcomas (EMC), poorly differentiated chordomas (PDC), malignant rhabdoid tumors, cribriform neuroepithelial tumors (CRINET), pleomorphic xantoastrocytomas (PXA), gangliogliomas, high‐grade gliomas, ependymomas, and meningeal SMARCB1‐deficient tumors 5–8 . According to the clustering analyses, some of the abovementioned tumors were similar to the AR/RT molecular subgroups such as CRINET and AT/RT‐TYR, DMT, SMACRB1 mutant, and AT/RTMYC 3,5 .…”
Section: Discussionmentioning
confidence: 99%